The Role of Money Supply and Commercial Bank Branches in Economic Growth in West Africa - Anastesia Uzonna Ezewulu; Clement Ifebuolili Sunday Ezeanyeji (PT. BATARI EDU CALYA, 2026)
West African economies continue to face challenges in achieving sustainable economic growth, despite ongoing financial sector reforms aimed at improving access to credit and financial services. Limited banking infrastructure, inefficient allocation of liquidity, and uneven financial inclusion have constrained investment and productivity, raising questions about the effectiveness of traditional financial expansion measures such as money supply growth and commercial bank branch proliferation. The study examined the relationship between financial development and economic growth in West Africa using the augmented growth framework of N. Gregory Mankiw, David Romer, and David Weil, which extends the Robert Solow model by incorporating human capital. A dynamic panel model was estimated using the System Generalized Method of Moments developed by Manuel Arellano and Stephen Bond to address endogeneity and heterogeneity. Annual data (2004–2023) from 16 West African countries were analysed. Variables included GDP, financial inclusion indicators, investment, institutional quality, and human development. Pre-estimation and diagnostic tests ensured stationarity, validity, and robustness of results. The results showed no multicollinearity among variables, as correlations were moderate, with RGDP strongly related to GFCF (0.8568) and moderately to HDI (0.1633). Cross-sectional dependence tests (Pesaran = 3.295; Friedman = 37.841) confirmed dependence, leading to the inclusion of time dummies. System GMM results revealed strong growth persistence (0.998). Broad money supply (−0.0006) and commercial bank branches (−0.013) had significant negative effects on growth, suggesting inflationary pressures and banking inefficiencies. HDI showed a weak positive effect (0.380). AR(2) (0.390) and Hansen (0.268) tests confirmed model validity, leading to rejection of the null hypothesis. In conclusion, sustainable economic growth in West Africa requires not only financial sector expansion but also improved financial intermediation, effective monetary management, and inclusive access to financial services. Policymakers should focus on combining monetary stability with human capital development and targeted financial inclusion strategies.